MUTU PERGURUAN TINGGI: PERSPEKTIF PERINGKAT UNIVERSITAS GLOBAL DAN AKREDITASI PERGURUAN TINGGI DI INDONESIA - Mulyoto Mulyoto; Unifah Rosyidi; Rugayah Rugayah (Manajemen Pendidikan, 2023)
World Class University (WCU) is the dream of all universities in the world, one of the indicators is the global ranking of universities carried out by university rating agencies in the world. The purpose of this study is to explore how the quality of higher education in Indonesia is viewed from the perspective of accreditation and university rankings at the world level. The methodology used is literature studies analysis and other documents. The focus of the analysis is on the official website of university ranking system at the global level and other media announcements to evaluate the relationship between university rankings and college accreditation on the quality of universities. The results of the study are 1). There is no standard indicator of measuring the quality of education as an objective general guideline. 2). Even though the international university rating agencies have different methodologies, both categories and performance indicators used, they have a relationship with the achievement of quality measures. 3). Higher education rankings provide a quantitative external view of the transparency of higher education institutions while quality assurance instruments cover both external and internal institutions. The Government and other policy makers should pay attention to the accreditation factor and the quality assurance system of these universities in making strategic policies, not only by looking at the ranking of universities at the global level.